Belichte Mensen : IV - Lauwaert, Dirk (Antwerpen : Andere Sinema, 1993)
Levitt, Helen ; Kertész, André ; Capa, Robert ; Scianna, Ferdinando ; Davies, John ; Hoeppe, Noelle ; Stieglitz, Alfred ; Weston, Edward ; Plossu, Bernard ; Hers, François ; Outerbridge, Paul ; Friedlander, Lee
Schenking Eric de Kuyper
boek